5-Hydroxy 6,2'-Dimethoxy isoflavone 7-O-β-D-galacotopyranoside from the Stem Bark of Antirheumatic Plant Liriodendron tulipifera Linn - Kumar Kuanar, Saroj (Asian Journal of Chemistry, 2010)
The glycoside 5-hydroxy 6,2´-dimethoxy isoflavone 7-O-β-D-galactopyranoside has been isolated from the stem bark of Liriodendron tulipifera Linn. This glycoside has been identified by chemical degradations and spectral analysis.